Development of an e-module containing ethnomathematics in the Problem Based Learning (PBL) model to improve elementary school students' problem solving abilities - Ula, Mutamimatul; Mastur, Zaenuri; Ridlo, Saiful (Tennessee Research International of Social Sciences, 2024)
The research aims to determine the character, validity, practicality and effectiveness of e-module products containing ethnomathematics in the problem based learning (PBL) model. RnD research uses a 4D model (define, design, develop and disseminate). The research subjects consisted of a small group of 24 students from SDN 1 Plantaran and a large group testing the effectiveness of the media with a total of 53 students, namely from SDN 1 Sukomulyo a total of 27 students and SDN 3 Protomulyo a total of 26 students in mathematics subjects with material Building Spaces, Cubes, Blocks and the combination. The effectiveness test uses the n-gain value and independent t test with a significance level of 5%. The results of the research show that 1) E-module learning media products containing ethnomathematics with the Problem Based Learning learning model, 2) E-module products containing ethnomathematics were assessed as appropriate by material experts with a percentage of 99% in the very feasible category, media experts with a percentage of 96% in the very category. worthy, the teacher's assessment of the learning process shows 87% in the very good category. 32 students responded very practically. 3) The use of e-modules containing ethnomathematics in the problem based learning model in mathematics learning increases students' problem solving abilities higher than students who do not use e-modules. The average n-gain score of experimental class students was 69.46 and control class students was 47.93 with the problem solving ability of 17 students in the high category in the experimental class.